PROCESSES OF REALIZATION OF KARAKALPAK FOLKLORE IN SYMPHONIC MUSIC OF 1990-2010 OF XX-XXI CENTURY - Jamil Charshemov (Western European Studies, 2024)
The aim of this article is to reveal the originality of Karakalpak composers' approaches to folklore, comparing their methods and techniques with those of their predecessors and contemporaries in other national schools, separating individuality from the typological features of the school and species traits of the direction
Keywords: Symphony; symphonic music; symphonietta